(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
Investigations results of technical state of bearing structures, bases and foundations of historical building in complicated conditions are presented. Stress strain state (SSS) of the «base – superstructure on piles – historical buildings» system was evaluated. Calculation by finite element method (FEM) using elastic perfectly-plastic Mohr – Coulomb soil model was applied. The most rational construction option taking into account the actual technical state of historical building was chosen. Test calculations have been made in order to determinate the possibility of loss of cultural heritage object of local significance due to three most likely accidents variants during operation of a new building. New building frame stability has been evaluated taking into account the local failure in case of emergency.